PENGARUH PEMBIAYAAN DANA MUDHARABAH DALAM MENSEJAHTERAKAN PARA NASABAH UMKM BERDASARKAN PRESPEKTIF MAQASHID SYARIAH - Hilmy Zein; Sri Herianingrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to examine the effect of mudharabah funding on the welfare of umkm customers based on Maqashid Syariah with variabel religion(ad-din), soul(an-nafs), sense(al-aql), offspring(an-nasl) and treasure(al-maal). The sample of this study is customers of mudharabah fund financing bank jatim syariah merr surabaya as many as 51 respondents. The data use are primary data collected using a questionnaire spread directly to customers umkm. Indicators of research variables are measured using likert scales 1 to 5. This research proves that mudharabah funding results have a significant positive effect on the welfare of customers based on maqashid sharia with religious variables religion(ad-din), soul(an-nafs), sense(al-aql) and treasure(al-maal), but on financing Mudharabah funds offspring variables (an-nasl) the results have a significant negative effect.Keywords: Mudharabah fund financing, Maqashid Syariah “ad-din, an-nafs, al-aql, an-nasl & al-maal.REFERENCESAscarya. 2007. Akad dan Produk Bank Syariah. Jakarta: PT Raja Grafindo Persada.Ali, Hamdani. 1986. FilsafatPendidikan. Yogyakarta: Kota KembangAntonio, Muhammad Syafi’i. 2001. Bank Syariah dari Teori ke Praktik. Jakarta: GemaInsani.Abdullah Saeed, Bank Islam dan Bunga: Studi Kritis Larangan Riba dan InterpretasiKontemporer, (Yogyakarta: Pustaka Pelajar, 2003), h. 91Hendi Suhendi, 2002, Fiqih Muamalah, Raja grafindo persada, Jakarta, hlm.136.http://jatim.bps.go.id/datastatistik/jawatimurkotasurabaya.434766, Diakses Pada 17 Febuari 2019. Http://ojk.go.id/id/kanal/iknb/Pages/Lembaga-Keuangansyariah, diakses pada 20 Januari 2019 Karim, Adiwarman. 2001. Ekonomi Islam, SuatuKajianKontemporer. Jakarta: GemaInsaniMujahidin, Akhmad, Ekonomi Islam: Sejarah, Konsep, Instrumen, Negara, dan Pasar,(Jakarta: Rajawali Pers, 2013), Cet- ke-2, h.257.Muhammad, Akuntansi Bank syariah,(Yogyakarta: Trust Media, 2009), h. 56Muhamad Syakir. 2004. Teknik PerhitunganBagi Hasil dan Profit Margin pada Bank Syariah. Yogyakarta: UII Press.Tadjab. 1994. PerbandinganPendidikan. Surabaya: KaryaAbditama.Todaro, Michael P. dan Stephen C. Smith.2003. Pembangunan Ekonomi di DuniaKetiga, edisikedelapan.Jakarta: Erlangga.Undang-Undang Republik Indonesia No. 20 tahun 2008 pasal 1 dan 6 tentang Usaha Mikro, Kecil dan Menengah.Undang-Undang Republik Indonesia No. 10 tahun 1998 tentang pengertian bank syariah.Undang-Undang Republik Indonesia No. 11 tahun 2009 tentang kesejahteraan sosial dan kesejahteraan UMKM.Undang-Undang Republik Indonesia No. 21 tahun 2008 tentang tugas lembaga keuangan syariah.Undang-Undang Nomor 1 Tahun 2013 tentang Lembaga Keuangan Mikro.